A network-centric approach to drugging TNF-induced NF-κB signaling - Nicolas A. Pabon (Nature Portfolio, 2019)
Chemical perturbation of specific protein–protein interactions is notoriously difficult, yet necessary when complete inhibition of a signalling pathway is detrimental to the cell. Here, the authors use a systems approach and identify two first-in-class small molecules that specifically inhibit TNF-induced NF-κB activation.